EFEKTIVITAS PEMBERIAN KITOSAN PADA PAKAN TERHADAP ORGANOLEPTIK IKAN LELE DUMBO (Clarias gariepinus) - Syahputra, Nanda; Febri, Suri Purnama; Komariyah, Siti; Haser, Teuku Fadlon; Aprita, Ika Rezvani (University of Prof. Dr. Hazairin, SH, 2023)
The cultivation of dumbo catfish (Clarias gariepinus) has great potential to be a profitable business as long as farmers can overcome obstacles such as odors in ponds and fish. Maintenance ponds that are not paid enough attention to make the aroma of the resulting dumbo catfish slime stronger. In overcoming this problem, we need a material that can reduce the odor in dumbo catfish. One natural ingredient that can improve water quality and reduce odor in catfish is by mixing chitosan in the feed. The purpose of this study was to evaluate the effectiveness of chitosan in removing odors and to determine the best dose of chitosan for eliminating odors in dumbo catfish. This study used an experimental method with a completely randomized design (CRD). The treatments used were (P0 = without chitosan; P1 = 2% chitosan; P2 = 4% chitosan; P3 = 6% chitosan, with 3 repetitions for each treatment). Parameters observed included organoleptic tests including aroma, texture, and taste to determine the effect of chitosan on dumbo catfish meat. The results of the study showed that the addition of chitosan to feed had a significant effect on eliminating odors in the organoleptic (aroma, texture, taste) of African catfish. The best dose of chitosan to remove odor in dumbo catfish (Clarias gariepinus) is at P2 (dose 4%) and P3 (6%).